Efisiensi Penggunaan CBC Calculator sebagai Alat Bantu Pengukuran Produktivitas Metode Crew Balance Chart - Aziz, Muhammad Abdul; Januardi, Redityo; Aliim, Muhammad Syaiful (PT Penjaminan Infrastruktur Indonesia (Persero), 2024)
Work productivity in construction project operations is often measured using non-scientific methods due to the relatively short time required. Productivity is typically calculated based on daily production output, which is measured in the afternoon. One scientific method for measuring productivity is the Crew Balance Chart (CBC). This study aims to evaluate the efficiency that can be achieved through an Android-based application specifically designed to streamline data processing and reduce measurement time. The method used is a comparative analysis of productivity measurement duration by comparing standard CBC methods with the tools, using a tower crane operation as a case study. The findings reveal an efficiency increase of 142.1%. The use of the Android-based application reduced measurement duration by 1,11 hours, from 3,76 hours to 2,64 hours. It is important to note that the application assists only in the data processing stage, while data collection and analysis continue to follow standard CBC procedures.